Identifying Best Practices to Improve Evaluation and Management of In-Hospital Stroke: A Scientific Statement From the American Heart Association. Issue 4 (9th February 2022) - Nouh, Amre; Amin-Hanjani, Sepideh; Furie, Karen L.; Kernan, Walter N.; Olson, DaiWai M.; Testai, Fernando D.; Alberts, Mark J.; Hussain, Mohammed A.; Cumbler, Ethan U.; ,
Abstract : This scientific statement describes a path to optimizing care for patients who experience an in-hospital stroke. Although these patients are in a monitored environment, their evaluation and treatment are often delayed compared with patients presenting to the emergency department, contributing to higher rates of morbidity and mortality. Reducing delays and optimizing treatment for patients with in-hospital stroke could improve outcomes. This scientific statement calls for the development of hospital systems of care and targeted quality improvement for in-hospital stroke. We propose 5 core elements to optimize in-hospital stroke care: 1. Deliver stroke training to all hospital staff, including how to activate in-hospital stroke alerts. 2. Create rapid response teams with dedicated stroke training and immediate access to neurological expertise. 3. Standardize the evaluation of patients with potential in-hospital stroke with physical assessment and imaging. 4. Address barriers to treatment potentially, including interfacility transfer to advanced stroke treatment. 5. Establish an in-hospital stroke quality oversight program delivering data-driven performance feedback and driving targeted quality improvement efforts. Additional research is needed to better understand how to reduce the incidence, morbidity, and mortality of in-hospital stroke.